Wet Granulation in a Twin Screw Extruder - Sun, Junfeng (My University, 2008)
This thesis covers a systematic examination of wet granulation in a twin screw extruder. Granulation of the excipient, (alpha)-lactose monohydrate, was done with the aid of PVP in an aqueous solution which acted as a binding agent. The influences on agglomeration by the following processing parameters were studied: screw elements design, screw rotational speed, binding solution concentration, and binder addition method. Qualitative efforts had also been made in modeling the process to gain valuable insight into how the elements affected agglomeration and granule rupture. A commercial software package PFC^2D, based on the Discrete Element Method (DEM), was used to simulate the dynamic behavior of the screw elements in the barrel. Within the optimal range of 7.5 -10wt% binder concentration, all the screw profiles were studied for their capacity to produce desirable granules suited to solid oral dosage form production. By increasing the rotational speed from 30 RPM to 80 RPM, the granules size of the conveying, discharging and chopping elements decreased whereas this operating parameter had little effect on granule size within kneading blocks. The nominal particle size produced by a screw element increased from 300(mu)m to 1mm when dispersive mixing was its dominant purpose (i.e. the kneading block), thereby meeting our criteria for a suitable granule in tab letting. Similar size development of the granules was not found with the other conveying or distributive mixing elements. In regards to particle shape, the kneading blocks produced elongated shape granules while other elements tested in this study produced smaller, more spherical agglomerates. Either shape was found effective in tabletting. Wet granulation was not feasible with more extreme concentrations of the aqueous binder (i.e. 5 wt% or 12 wt%) in this project, and the hand pre-blend method was the only approach found suitable for metering this additive into the system while maintaining steady feeding rates and output.
Keywords: granulation; twin screw; screw; extruder